G. Hauptmann’s novel «Phantom» and its cinematic embodiment - Alexander Voronovsky (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article deals with the theme of the interaction of literature and emerging cinema on the example of the work of the prominent German writer Gerhart Hauptmann (1862–1946). He was one of the first to see in the new art new opportunities for self-expression. Hauptmann’s attitude to cinema was ambiguous and changed over the years, but finally his direct involvement in the film adaptations of his works determined the nature of his artistic pursuits. Inspired by the new ideas the German writer returned to his unfinished novel «Phantom» (Phantom, 1922). Despite the exact reproduction of the storyline, the film director Friedrich Wilhelm Murnau and screenwriter Thea von Harbow adapted seriously Hauptmann’s work to their needs. In particular, the accents in the interpretation of the problem of individual freedom are changed, the central character is viewed differently. The director, using brilliantly the visual possibilities of cinematic art, emphasizes the themes and motifs crucial for Hauptmann. Murnau stresses the role of the unconscious discussing the origins of the spiritual enslavement of individual. The director shows how the person loses his self-control due to irrational forces. In the film he demonstrates the private world of the «nervous» person, moving away from the external reality into the world of hallucinations. He shows the central character frustrated and confused in front of the subconscious. In addition, Murnau, unlike Hauptmann, associates the human loss of self-control with the late 19th and early 20th century popular problem of the war of the sexes with its irrational and even demonic elements. Hauptmann’s novel, initially coldly received by critics who reproached the writer for its predominantly entertaining nature, was later reevaluated largely because of Murnau’s interpretation